Modern Justice: Indonesia’s Supreme Court’s Challenges to Uphold Fair Trial Principles Through Digitalization - Sibarani, William Edward (Faculty of Law, Universitas Brawijaya, 2023)
As we have seen, it is essential to widen digitization in order to bestow better access to public information contained in Indonesian courts for a variety of purposes. Court modernization through digitization benefits not only the judges but also both attorneys and litigants. To this end, Indonesia’s Supreme Court has progressed above and beyond to embody the principle of equality before the law by integrating technological development into the judicial process with. In fact, qualified policies do not always govern the implementation of technology, resulting in discrepancies between policy and implementation. Using a statutory, case, and historical approach, these article will assess whether it is reasonable and efficient to adopt this technology in Indonesian courts. Qualified implementing regulations and tiered socialization have not been utilized in the judicial context to support law enforcement’s readiness to carry out the judicial process electronically. This article further addresses the safety of personal and judicial data, and the security of electronic court proceedings, bearing in mind that applications of information technology should be considerate of the community’s need for access to justice as well as the court’s interests in preserving its authority. Nonetheless, given that technology has already been implemented to enhance access, a variety of actions aimed at bolstering both policy issuance and reforming the technological infrastructure will encourage the court to conduct trials in a safe and sound manner.